The Development of Children's Independence at Fadhilah Amal 3 Kindergarten, Dadok Raya Padang - Puji Lestary; Serli Marlina (Program Studi PGRA, 2019)
The purpose of this study was to describe the development of children’s independence at Kindergarten of Fadhilah Amal 3, Dadok Raya District, Padang. This type of research is qualitative research with descriptive methods. Researchers use principals and teachers as research informants. The collect data method through observation, interviews, and documentation. The research data analysis technique is done by data triangulation technique. Children’s independence in Kindergarten Fadhilah Amal 3 Dadok Raya Subdistrict Padang can be seen in all activities carried out children daily, such as when the first child arrives at school when they learn in the classroom and plays outside. The results showed that various forms of children’s independence such as choosing work to be done firstly, choosing their own favorite game, playing alone without being accompanied by a teacher, doing their own daily activities without the help of others. Suggestions from researcher to parents and teachers to be able to teach children to get used to being independent in doing everything.